The challenges of instructional leadership in Manitoba First Nations schools: an exploration of what principals have to say - Scott, Margaret R. (2017)
The focus of this study deals with the perceptions of principals employed by band-operated First Nations (FN) schools in Manitoba. The study explored their educational leadership, especially with respect to their ability to lead in the midst of numerous unique challenges. I argue that these challenges make it difficult for principals to devote sufficient time and energy to instructional leadership. A review of the relevant literature indicates that principals with positive instructional leadership practices can improve student achievement levels. I also argue that improved instructional leadership may result in higher graduation rates. High school graduation is a common indicator used to measure the success of FN schools. The 2004 Auditor General’s report estimated that it will take 27 years for FN school graduation rates to catch up to Canadian mainstream rates. Currently, FN schools in Manitoba are without the sort of legislative framework that is provided by the Manitoba Public Schools Act for provincial schools. While governments in British Columbia and Nova Scotia have adopted legislative frameworks for their FN schools, FN schools in other provinces have not benefited from similar legislation. Would a legislative framework in Manitoba’s First Nations schools provide the necessary conditions to exercise more effective instructional leadership for improved student learning? Western curricular frameworks currently dominate teaching and learning in FN schools. Would principals prefer a more culturally appropriate curriculum? Would such a curriculum improve student engagement and, ultimately, graduation rates in FN schools? A qualitative research methodology “to understand the meaning of events and interactions to ordinary people in particular situations” (Bogdan & Biklen, 2007, p. 25) was used to determine if and how the unique challenges faced by FN school principals affect their instructional leadership. October 2017